2015
DOI: 10.26719/2015.21.412
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of diabetes mellitus in a central district in Islamic Republic of Iran: a population-based study on adults aged 40–80 years

Abstract: Previous studies on type 2 diabetes mellitus in the Islamic Republic of Iran were mainly performed in provinces with large populations. This study determined the prevalence and risk factors of diabetes mellitus in an adult population (40-80 years old) from Yazd district. Multistage, systematic cluster random sampling was used in a crosssectional, population-based survey. Demographic, clinical and anthropometric data were collected, with diabetes defined as fasting blood sugar ≥ 7 mmol/L or a positive medical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…According to the results, the DM prevalence in this study was less than the national estimate of 15.0% in Iran in 2021 13 . Similar studies with the same age groups, in Shahroud (12%) 23 , Ahvaz (15%) 24 , and Yazd (24%) 25 reported a higher proportion, and Ravansar in Kermanshah (8.19%) 6 and Valashahr in Fars (9.19%) 26 reported less prevalence of diabetes. Also, this prevalence was still fewer than that of Afghanistan 27 , and Pakistan 28 and higher than that of Bangladesh 29 and Nepal 30 .…”
Section: Discussionsupporting
confidence: 74%
“…According to the results, the DM prevalence in this study was less than the national estimate of 15.0% in Iran in 2021 13 . Similar studies with the same age groups, in Shahroud (12%) 23 , Ahvaz (15%) 24 , and Yazd (24%) 25 reported a higher proportion, and Ravansar in Kermanshah (8.19%) 6 and Valashahr in Fars (9.19%) 26 reported less prevalence of diabetes. Also, this prevalence was still fewer than that of Afghanistan 27 , and Pakistan 28 and higher than that of Bangladesh 29 and Nepal 30 .…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of DM in Yazd province in the population over 30 years old was reported from 13.8% in 1998 to 16.3% in 2012 [13,14]. Recent studies have reported the prevalence of the DM in 40-80-years old group 24.5% [15]. However, no comprehensive, current and representative data is available for this prevalent disease in Yazd.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with previous studies. [25][26][27] Also, the rural dwellers in our study were older, had poor education, were mostly unemployed, had a higher frequency of HTN, and had a poor wealth index compared to urban residents (data not shown). The factors mentioned above are important risk factors for diabetes and pre-diabetes and can explain the higher prevalence of DM and IFG in rural residents in our study.…”
Section: Discussionmentioning
confidence: 69%